Thermo-hydro-mechanical effects on host rock for a generic spent nuclear fuel repository (Rudarsko-geološko-naftni zbornik, 2019)
After the adoption of the National Program for the Implementation of the Strategy for the Management of Radioactive Waste Used Resources and Spent Nuclear Fuel, by the Government of the Republic of Croatia, the issue of radioactive waste management in Croatia became current. Slovene-Croatian co-ownership over the Krško nuclear power plant (KNPP) means that half of the operational and decommissioning waste, as well as spent nuclear fuel (SNF) belongs to Croatia. Until now, SNF has been kept in a pool at KNPP, and dry storage before disposal is also planned. A generic project of a SNF repository has been developed and has already undergone a second revision and review. The project idea in- volves site selection in both countries and the conceptual solution of the SKB-3V type in crystalline rock. This paper presents an estimate of the thermal-hydro-mechanical effects (THME) of the SNF repository in crystalline rock (grano-diorite) of SKB-3V concept by developing a numerical model in the SIGMA/W, SEEP/W and TEMP/W software. Simula- tions have shown that it is possible to construct a SNF repository in the crystalline rocks of Croatia or Slovenia, that the generic repository project is well-designed and that a model of hydro-thermo-mechanical effects of spent nuclear fuel on the rock in Croatia/Slovenia can be produced, which proves the suitability of the rock mass for this purpose.